PERANCANGAN PARAMETER PI-DIGITAL DENGAN METODE MODULUS OPTIMUM PADA DIRECT TORQUE CONTROL MOTOR TRAKSI INDUKSI TIGA FASA - Dewi Sukma S.Y; Moch. Rusli; Bambang Siswojo (Jurnal Mahasiswa TEUB, 2023)
In accordance with technological developments, induction motor control is important in the industrial field. The desired control is to obtain a motor speed response that matches the setpoint. This study uses the specifications of a three-phase induction traction motor, one of which is used in fast trains. Rugged and simple motor construction, high efficiency, easy maintenance, and economy are advantages in the use of three-phase induction motors. The control vector method used is the DTC method with the SVM technique in Simulink Matlab software. This study uses a PI controller with the MO tuning method. The controller parameter values for the speed control loop are Kp = 458.3, Ti = 0.5, and Ki = 916.6. The controller parameter values in the torque control loop are Kp = 1.2, Ti = 0.5, and Ki = 2.4. The controller parameter values in the flux control loop are Kp = 74.9, Ti = 0.49, and Ki = 152.9. This study has simulated and analyzed the response of the PI-Digital controller circuit with the MO tuning method on the DTC three-phase induction traction motor under zero/no load conditions which produces an output response in accordance with specified design specifications, where the output speed is 158.5 rad/s with a settling time of 0.17 seconds and a steady state error of 0.9%. As well as under torque load conditions of 100 N.m, 200 N.m, and 300 N.m, the output generated with the settling time is longer with an additional time of 0.01 second. Keywords: three-phase induction traction motor, direct torque control (DTC), Space Vector Modulation (SVM), PI controller, Modulus Optimum (MO), simulink. DAFTAR PUSTAKA[1] N. Pimkumwong and M.-S. Wang, "Direct Torque Control of Three-Phase Induction Motor based on Constant Voltage per Frequency Control with Simple Controller," International Conference on Electrical Engineering/Electronics, Computer,Telecommunications and Information Technology, 2018.[2] N. Evalina, A. A. H and Zulfikar, "Pengaturan Kecepatan Putaran Motor Induksi 3 Fasa Menggunakan 8 Programmable logic controller," Journal of Electrical Technology, 2018. [3] M. Vítečková and A. Víteček, "Modulus optimum for digital controllers," Acta Montanistica Slovaca, 2003.[4] M. S. A. Sari, H. Suyono and A. Lomi, "Analisis Kendali Kecepatan Motor Induksi 3 Fasa dengan Metode Direct Torque Control (DTC) Berbasis PID Kontrol," ECOTIPE, pp. 70-77, 2020.[5] K. L. Shi, T. F. Chan, Y. K. Wong and S. L. Ho, "Modelling and Simulation of Direct Self-Control Systems," Int. J. Engng Ed., pp. 646-654, 2003.[6] T. Ramesh and A. K. Panda, "Direct Flux and Torque Control of Three Phase Induction Motor Drive Using PI and Fuzzy Logic Controllers for Speed Regulator and Low Torque Ripple," IEEE, 2012.[7] O. C. Sekhar, S. Lakhimsetty and A. H. Bhat, "A Comparative Experimental Analysis of Fractional Order PI Controller Based Direct Torque Control Scheme for Induction Motor Drive," Int Trans Electr Energ Syst., 2020.[8] M. Yusuf, V. Prasetia, S. D. Riyanto and A. A. Rafiq, "Desain Simulasi Sistem Pengaturan Kecepatan Motor Induksi Tiga Fasa dengan Switching Space Vector Pulse Width Modulation," ECOTIPE, pp. 24-31, 2019.[9] D. Rabie, Y. S. Mohamed and E. G. Shehata, "Voltage Source Converter Control and Stability Analysis of VSCHVDC System with High DC-Link Impedance," International Middle East Power Systems Conference (MEPCON), 2019.[10] A. A. Z. Diad, "Implementation of a novel full-order observer for speed sensorless vector control of induction motor drives," springer, 2017.[11] S. Enache, A. Campeanu, I. Vlad, R. Zlatian and M. A. Enache, "Dynamic Analysis of New Induction Motor for Electrical Traction," International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2020.